Implementasi File Server Terintegrasi dengan Active Directory pada SMP Bani Taqwa Kota Bekasi: Indonesia - Danil Tanjung; Heri Haerudin (CV. Multi Kreasi Media, 2022)
SMP Bani Taqwa Kota Bekasi currently has hardware that is connected to the internet and computer networks, but does not yet have a file server as a means of storage and to share resources on an integrated network with Active Directory. The server that will be built certainly needs to be maximized by using the Active Directory Domain Services role function in order to facilitate the work of an administrator in managing and dividing user and group access rights. The purpose of this study is to implement the use of a file server as a storage facility and to share resources on a network that is integrated with Active Directory to manage and share user and group access rights on computer networks at SMP Bani Taqwa Kota Bekasi. The method used in this research is PPDIOO (Pepare, Plan, Design, Implement, Operate, and Optimize) which is a network design method from Cisco as a life cycle in network services in supporting the development of computer networks. The expected result of this research is to make it easier for users to share resources on a file server, limit access rights between sections on a computer network, and simplify the work of administrators at SMP Bina Taqwa Kota Bekasi.